Pengaruh Brand Experience, Value dan Brand Loyalty terhadap Pengguna Handphone Iphone di Jakarta Barat - Haidar Haidar; Benny Gunawan (JURNAL RISET MANAJEMEN (JURMA), 2025)
The rapid development of information and communication technology has caused significant changes to people's lives, especially in terms of communication. The needs of society in this era of globalization in the form of smartphones are high because technology continues to develop. This study aims to determine the influence of Brand Experience value and brand loyalty to Iphone smartphone customers In this study, the population studied is all people who buy and use iPhone smartphones. The sample in this study amounted to 100 people who were collected and then processed using the multiple linear regression method, the results of the study showed. Brand experience, Value and Brand Loyalty together affect Iphone users means that if Brand experience value and brand loyalty are increased according to consumer wishes, iPhone enthusiasts will have more Brand experience affecting Iphone users if the price value offered by the Iphone is in accordance with the benefits received, it will increase Iphone users Brand loyalty is very influential on Iphone users, customer loyalty to the Iphone is very calculated, meaning that if customer loyalty is dominant it will increase iPhone users